A novel comprehensive model for predicting production of downhole choke wells. (1st April 2022) - Xie, Chuan; Liu, Yonghui; Li, Xiaoping; Wu, Ning; Luo, Chengcheng; Bill Zeng, Fanhua
Graphical abstract: Highlights: A novel model for predicting the mass flow rate through downhole choke is proposed. Compared with existing models, the new model reduces the AAPD from 30.1% to 3.7%. Slip factor between gas and liquid phases affect the accuracy of the prediction results of the new model. The flow pattern in the upstream of the choke can be identified by the pressure drop across the choke. Abstract: The mass-flow rate that flows through wellhead/downhole chokes is typically used to measure oil/gas production. Published mass-flow rate prediction models are proposed based on wellhead choke data; however, because of the different flow behavior between vertical and horizontal tubes, unacceptable errors may occur when used on downhole choke wells. These models can be improved by three additional factors; flow patterns, gravity, and gas expansion coefficient. In this study, 180 pressure, mass-flow rate, and flow pattern data points were measured with four different size chokes on a vertical tube. According to the flow behavior analysis, a new comprehensive model was proposed to improve the accuracy of multiphase mass-flow rate prediction for downhole chokes. The experimental results show that the downhole choke redistributes the gas and liquid phase, causing the flow patterns downstream of the choke to change. Additionally, pressure data analysis results show that the pressure difference between the Pu (pressure upstream of the chokes) and Pd (pressure downstream of the chokes) can be used to identify the flow pattern transitions upstream of the chokes. The statistical error results of the new model coupled with various slip models reveal that the Simpson (RMSE = 0.0018 Kg/s, R 2  = 0.99) and Schuller (RMSE = 0.002 Kg/s, R 2  = 0.97) models achieve the highest accuracy prediction for the intermittent and continuous flow, respectively. Furthermore, the critical pressure ratio measured on a vertical tube can be accurately predicted by the new comprehensive model. Compared to other models, the new comprehensive model is the most accurate, yielding the best mass-flow rate predictions for the dataset; slug (RMSE = 0.0018 Kg/s and R 2  = 0.98), churn (RMSE = 0.0018 Kg/s and R 2  = 0.99), and annular flow conditions (RMSE = 0.002 Kg/s and R 2  = 0.97).